Clinical efficacy of Shatapushpa (Anethum sowa Kurz.) powder in the management of Artava kshaya (oligomenorrhoea) - Ghose, A. (Medknow Publications Pvt Ltd, 2010)
A clinical trial was carried out on 30 oligomenorrhoea [Artava Kshaya] patients aged between 15 and 35 years having complaints of irregular, scanty and painful menstruations. The patients were registered from OPD and IPD of Gopabandhu Ayurveda Mahavidyalaya Puri. They were administrated Satapuspa churna for three months in a dose of 5 g twice daily with cow grita. The specific investigations were done in order to exclude TB endometritis, endocrine disorders, diabetes and heart disease. The clinical assessment was carried out in thirty days intervals. It is inferred that the study discloses the effect of satapuspa churna on irregularity of interval of menstruation [90.47%], duration of menstruation [79.37%], amount of blood flow [90.00%] and pain during menstruation [100.00%] which were highly significant in clinical study. No untoward side effect was noticed during clinical trial.